Integration of UiTM Perak Campus with Tourism Malaysia Perak as an Academic Community - Man, Mohamad Sohaimi (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018), 2018)
Tourism is a unique product and a mixture of tangible and intangible elements and an inspiration in daily life activities. It is recognized as an economic catalyst and the generation of local, state and country through the diversity of attractions such as the impact of heritage, natural beauty of Allah SWT creation until the culture and behaviour of the local community. This is an existing asset as commercialist products in the promotion of tourism industry in the country. Following that, a tourist attraction for coming to our country can be processed and innovated through the integration of three components namely as universities, travel agencies and local communities. Such integration can create partnerships towards centering elements of local history from various aspects such as visual arts, cultural and environmental patterns. University became the main role is to be realized as the first tourist destination before heading to any other destination. Rationally, Universiti Teknologi MARA Cawangan Perak can serve as a transit centre for academic information academic commercialization patterned tour through cooperation with travel agencies and local communities. This is an academic innovation that can be implemented through a mechanism that is to bring the university to the community and not community to the university. This is an added value in enhancing the delivery of information to be shared with the public interest, in line with the university's objective to improve relations and cooperation with international organizations in the activities of the network in the industry to help the country through the promotion of the tourism industry. These efforts will be successful if there is extensive involvement of the university community and travel agencies, local communities, state governments and government agencies or the private sector is prepared to give a commitment and cooperation at its best communities. Keywords: integration, university, transit travellers